Research the Degradation Process of Solar Panels Based on Polycrystalline Silicon in the Climatic Conditions of Uzbekistan During Several Years of Operation - Odamov, U.O.; Kоmilov, M.M.; Obidova, Z.N.; Raxmonov, V.T.; Kurbonova, D.A.; Pirmatov, S.; Medetova, M.M.; Mustafakulova, Kh.A. (Journal of Ecohumanism, 2025)
The article researches the degradation processes of PV panels at the 130 kW Namangan-Pop Solar photovoltaic plant (SPVP) as a result of seasonal climate effects. All PV panels installed in the SPVP are HSL 250, JSMM 2501, SM250 PC 8 and TS-S 400 polycrystalline solar panels manufactured by South Korean companies HANHWA, JSPV, S-ENERGY and TOPSUN. Among them, degradation processes were observed in HANHWA HSL 250 type solar panels. These degradation processes have been determined based on experimental researches based on the requirements of the International Standard. The comparison of the volt-ampere characteristics and power-voltage graphs of HANHWA's defective and new unused HSL 250 solar panels are presented. In Namangan-Pop Solar photovoltaic plant, reference (Yr) and final (Yf) production during the study period are averaged 4.12 hours and 3.67 hours per year, respectively and the production ratio (PR) varies between 87.24% - 93.58% and the average annual production ratio (PR) is 87.28% and the rate of degradation of SPVP between 2015-2021 was determined to be 0.224% per year on average.